2015
DOI: 10.1039/c4tb01956c
|View full text |Cite
|
Sign up to set email alerts
|

Structural impact of graft and block copolymers based on poly(N-vinylpyrrolidone) and poly(2-dimethylaminoethyl methacrylate) in gene delivery

Abstract: The characteristics of graft and block copolymers based on PVP and PDMAEMA in pDNA compaction, cytotoxicity, transfection efficiency, internalization and intracellular distribution were systematically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…However, in this study, the REDV-PPP2/pZNF580 complex group showed lower transfection than the REDV-PPP1/pZNF580 complex group. 53 Although the zeta potential of complexes usually facilitates cellular uptake, our results have demonstrated that the REDV amount in NP/pZNF580 complexes also benefits to cellular uptake.…”
Section: Discussionmentioning
confidence: 56%
“…However, in this study, the REDV-PPP2/pZNF580 complex group showed lower transfection than the REDV-PPP1/pZNF580 complex group. 53 Although the zeta potential of complexes usually facilitates cellular uptake, our results have demonstrated that the REDV amount in NP/pZNF580 complexes also benefits to cellular uptake.…”
Section: Discussionmentioning
confidence: 56%
“…Up to now, PVP has been used in the pharmaceutical and biomedical fields to develop different drug delivery systems, such as oral, topical, transdermal, and ocular administration. Besides, PVP is also useful in the delivery of genes [8][9][10][11][12] or can be coupled with metal particles for regenerative medicine [13][14][15] and targeted-delivery [16,17]. Therefore, PVP results to also be a very versatile polymer.…”
Section: Introductionmentioning
confidence: 99%
“…As cationic components for polyplex formation, poly(ethylene imine), poly( N , N ‐dimethylaminoethyl) structures, poly( l ‐lysine) and several other structures that bear primary, secondary, tertiary or quarternized amines have been used frequently. [ 21–30 ] Incorporation of poly(ethylene glycol), poly(2‐oxazoline), or polysarcosine increases the solubility of the polyplex and further decreases interaction with blood components. [ 12,31–39 ]…”
Section: Introductionmentioning
confidence: 99%